Evaluating evaluators an evaluation of education in Germany - Harris-Huemmert, Susan 1963-; SpringerLink (Online service). (Wiesbaden VS Verlag für Sozialwissenschaften, 2011)
How do evaluators of higher education go about their work? How are groups of evaluators put together? How do they reach consensus on the criteria of quality in the discipline or degree programme under examination? What problems do evaluators encounter and how do they resolve them? Susan Harris-Huemmert investigates these questions in this detailed case study of an evaluation commission that inspected education departments in the German state of Baden-Württemberg (universities and teacher-training colleges) during 2003/2004. This work takes up not only topics germane to evaluators of higher education, but also illustrates the politics and contextual issues surrounding the discipline of education in Germany during the first decade of the 21st century. The book will be of interest to education researchers, students of evaluation, peer reviewers and those working in higher education quality assurance
Introduction Evaluation and Quality in German Higher Education Theory and Methods The Chronology of the Evaluation The Roles of Individuals and Their Work Ethics Establishing evaluation critieria: reaching consensus on the notion of quality in German Educational Science Organisational issues and problems: self-concept of evaluators and learning processes Review of the evaluation, critical discussion, and conclusions Developments in German HE quality assurance since 2004
Includes bibliographical references
Electronic reproduction
Keywords: Education, Higher -- Germany -- Evaluation